(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Keki N. Daruwalla and Nissim Ezekiel are two powerful voices of modern Indian English Poetry. Their literary communication is testament to their poetic ability and singularity. Though Ezekiel and Daruwalla are among the current Indian English Poets, yet Ezekiel is senior to Daruwalla by almost two decades. Ezekiel began writing in the 1950s whereas Daruwalla in the 1970s. Hence, the work attempts to discover the matching bonds between the two poets in order to analyse the poetic cosmos of the two distinct time periods and in what manner these two poets, representatives of their age, are paving the way for the upcoming poets. In contrast to Ezekiel, Daruwalla is influenced by the western style of writing, more given to language and poetic form. Furthermore, in both the poets the personal and subjective experiences go a long way in shaping their poetic communication. In this background, this paper aims to highlight the various similarities and differences in the poetic themes of Nissim Ezekiel and Keki Daruwalla. It conclude that, both the poets highlighted social, cultural, traditional, superstitious, religious, mythical attitudes of the society recaptured the Socio-cultural aspects of Indian society in a realistic manner. They also highlighted various techniques and styles of writing poetry in Indian English literature.